Pandangan Hakim Pengadilan Agama Palembang Terhadap Putusan Mahkamah Konstitusi Nomor 46/PUU-VIII/2010 Tentang Status Anak di Luar Nikah - Arne Huzaimah (Intizar, 2014)
Penelitian ini mengkaji tentang status anak di luar nikah perpektif hukum Islam. Pertimbangan Hukum Majelis Hakim Mahkamah Konstitusi Nomor: 46/PUU-VIII/201. Pandangan Hakim Pengadilan Agama Kelas 1A Palembang terhadap Putusan Mahkamah Konstitusi Nomor: 46/PUU-VIII/2010 adalah: Putusan uji materi pasal 43 ayat 1 UUP, sesungguhnya ditujukan untuk anak yang lahir di luar perkawinan akibat nikah sirri atau kumpul kebo. Berdasarkan penetapan pengadilan agama yang berkaitan dengan pengesahan perkawinan/itsbat nikah dan penetapan asal usul anak, maka anak yang dilahirkan dari perkawinan sirri dapat dinyatakan sebagai anak yang sah. Dengan status anak sah, maka anak tersebut mempunyai hubungan perdata dengan ayah biologisnya. Hubungan perdata yang timbul akibat dari adanya hubungan darah ini meliputi hubungan hukum, hak dan kewajiban antara anak dengan ayah dan ibunya yang dapat berupa:  (1)  hubungan  nasab;  (2)  hubungan mahram; (3) hubungan hak dan kewajiban; (4) hubungan pewarisan (saling mewarisi)  yang  merupakan  pelanjutan  hubungan  hak  dan  kewajiban karena  nasab  ketika mereka  sama-sama masih  hidup;  dan  (5)  hubungan wali nikah antara ayah dengan anak perempuannya.This paper examined the status of children outside wedlock in perspective of Islamic law. Consideration of the judges of the Constitutional Court Law No. 46 / PUU-VIII / 2010: included: the right to obtain legal status of the child; registration of marriage was not a factor in determining the legal of the marriage and registration of marriages was an administrative obligations required by legislation. The factors that determined the legal of a marriage was the conditions prescribed by the religion of each pair bride; problems concerned children born out of wedlock should receive law protection and law certainty to the status of a child born and rights available to him, including toward children born though the legal of the marriage still disputed. While the view of the religion Court Judge Class 1A Palembang to Constitutional Court Decision No. 46 / PUU-VIII / 2010: Decision of the judicial review of Article 43 paragraph 1 UUP, in fact intended for children born out of wedlock as a result of Sirri marriage or cohabiting. Based on the determination of religion courts that related to ratification of the marriage / marriage ithbat and determination of the origin of the child, then the child born of the marriage Sirri could be expressed as a legitimate child. With the status of a legitimate child, then the child had a civil relationship with biological father. Civil relations arose from the presence of this blood relationship included legal relationships, rights and obligations between the child with his/her father and mother who could be: (1) the relationship nasab; (2) the relationship of mahram; (3) the relationship of rights and obligations; (4) the relationship of inheritance (inherit each other) which was a continuation of the relationship of rights and obligations as nasab when they were both still alive; and (5) the relationship of guardians between a father with his daughter.